2006
DOI: 10.1080/09553000600972956
|View full text |Cite
|
Sign up to set email alerts
|

Radiation tolerance in the tardigradeMilnesium tardigradum

Abstract: M. tardigradum survives high doses of ionizing radiation in both hydrated and anhydrobiotic states, but irradiation with >1000 Gy makes them sterile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
129
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 13 publications
8
129
2
3
Order By: Relevance
“…Our data show the link between tps presence and trehalose production, as the gene was found in the same Richtersius coronifer population (previously cited as Adorybiotus coronifer) in which Westh and Ramløv (1991) first detected the synthesis of trehalose during the desiccation process. Moreover, our data support the possibility that the trehalose biosynthesis pathway can be functional in Milnesium tardigradum, as shown by the presence of trehalose found by Horikawa et al (2006) and Jönsson & Persson (2010). The absence of trehalose in M. tardigradum found by Hengherr et al (2008) could be due to the fact that the trehalose level in M. tardigradum is very low (Horikawa et al 2006;Jönsson & Persson 2010) and Hengherr et al (2008) may have underestimated its presence.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our data show the link between tps presence and trehalose production, as the gene was found in the same Richtersius coronifer population (previously cited as Adorybiotus coronifer) in which Westh and Ramløv (1991) first detected the synthesis of trehalose during the desiccation process. Moreover, our data support the possibility that the trehalose biosynthesis pathway can be functional in Milnesium tardigradum, as shown by the presence of trehalose found by Horikawa et al (2006) and Jönsson & Persson (2010). The absence of trehalose in M. tardigradum found by Hengherr et al (2008) could be due to the fact that the trehalose level in M. tardigradum is very low (Horikawa et al 2006;Jönsson & Persson 2010) and Hengherr et al (2008) may have underestimated its presence.…”
Section: Discussionsupporting
confidence: 54%
“…Trehalose was not detectable in one desiccation tolerant population (Hengherr et al 2008), a datum confirmed by further analyses on proteome and transcriptome Schokraie et al 2010), which did not evidence any transcripts of genes involved in trehalose biosynthesis. On the other hand, in other studies on different desiccation tolerant populations of the same species, trehalose was detected (Horikawa et al 2006;Jönsson & Persson 2010).…”
Section: Introductionmentioning
confidence: 97%
“…However, DNA may be the sensitive target of spores exposed to ultrahigh shock pressures (Moeller et al 2008). As another extreme example, tardigrades, which are among the most desiccation and radiation-tolerant animals, have been shown to survive extreme levels of ionizing radiation (Horikawa et al 2006), temperatures of −273°C (Becquerel 1950) and the vacuum of space (Jönsson et al 2008). Whereas microgravity and radiation had no effect on the survival nor DNA integrity of active tardigrades (Rebecchi et al 2009), after being exposed to the space environment for 12 days, tardigrades molted and females laid eggs (Rebecchi et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To survive drought, which occurs frequently in the habitat of moss-dwelling tardigrades, they enter a so-called tun state (Baumann 1922) and show strong resistance to physical extremes, including high and low temperatures (Ramløv and Westh 1992;Sømme 1996;Ramløv and Westh 2001;Hengherr et al 2009), high pressure (Seki and Toyoshima 1998), vacuum and ionising irradiation (Horikawa et al 2006;Jönsson et al 2008). In the anhydrobiotic state, their metabolism is barely measurable (Pigoń and Węglarska 1955).…”
Section: Introductionmentioning
confidence: 99%